Designing UI/UX App for Parents of ASD Children through Social Approach - Anggis Rizky Wiyaringtyas; Irma Damajanti (Universitas Islam Kuantan Singingi, 2024)
Compared to children’s parents with typical conditions, parents of children with autism spectrum disorder (ASD) experience higher levels of stress. As a result, parents may become more at risk of social stigma and become apart from those who seem can't understand their situation. Parents' stress levels can be reduced by experiencing a positive response like happiness and comfortable. One of the factors that makes parents of children happy and comfort with ASD is social support. In this study, researchers developed a smartphone application that can provide social support—such as groups, information, and emotional support—to parents who have children with ASD. The design thinking approach was implemented in this study, which involved collecting data via surveys, interviews, and observations to designing the UI/UX application during the ideation phase. According to the study's findings, parents nowadays need a parenting app that can make it easier for them to find social support.